Harmony Leadership and Personality on Employee Performance at Ganesha University of Education - Arief Billah; Ni Made Suci; I Nengah Suarmanayasa (International Journal of Social Science and Business, 2022)
The problem that is often faced is low employee performance. The purposes of this study are to analyse the effect of harmonious leadership on the performance of Undiksha employees, analyse influence on the performance of Undiksha employees and analyse the mutual influence of harmony and leadership on the performance of Undiksha employees. This type of research is quantitative. The population in this study were employees with the status of Civil Servants who had worked for at least five years at Undiksha, amount 240 people. Determining the sample in the study refers to the slovin formulation so that 150 samples are obtained. Data collection in this study was conducted by interviewing Undiksha employees and questionnaires about the harmony of leadership, personality, and performance of Undiksha employees. Data analysis was performed by multiple linear regression analysis. The results showed that, first, Harmoni's leadership had a positive and significant effect on the performance of Undiksha employees. Second, personality has a positive and significant effect on the performance of Undiksha employees. Third, leadership and personality that are aligned simultaneously have a positive and significant impact on the performance of Undiksha employees. Based on these findings, it can be said that there is a significant relationship between harmonious leadership and the activities of Undiksha employees, both separately and simultaneously. Thus, the second factor can be used as an employee predictor of performance levels at Undiksha.